Present solar energy potential and strategies in China - Solangi, K.H.; Rahman, S.; Rahim, N.A.; Fayaz, H.; Islam, M.R. (2011)
Facing great pressure of economic growth and energy crisis, China pays much attention to the renewable energy. Renewable energy development is one of the main targets of the Chinese government on the way to the sustainable development and climate change mitigation. China's energy policy target is to reach 15.4% renewable energy share by 2020 and 27.5% by 2050. China’s total installed electrical power capacity reached 700 GW by the end of 2007 and is predicted to surpass 900 GW in 2010. A similar goal exists for the solar photovoltaic power sector which China intends to increase generating capacity from 0.14 GW as of 2009 to over 1.8 GW by 2020. In order to achieve this target, the Government has implemented many instruments from laws and policies and financial incentives. The paper gives introduction to the present situation of the solar energy development in China and overviews the main policies that China uses to promote and develop the solar energy. Also, the suggestions for the further development of solar energy technologies in China are given.